A comparative analysis of innovation policies in Hong Kong and Shenzhen within the Greater Bay Area initiative. (8th September 2021) - Sharif, Naubahar; Chandra, Kevin
Abstract: Combining documentary analysis with hierarchical cluster analysis (HCA), we conduct a comparative study of innovation policies in two municipalities included in the Greater Bay Area (GBA) initiative—the Chinese government's plan to link eleven cities into an economic and business hub. After identifying innovation policies/agencies in Hong Kong and Shenzhen, we apply the HCA to compare similarities and differences between their innovation policies and assess how these policies align with the 'cross-border regional innovation system' (CBRIS) conceptual approach. We find that Hong Kong's innovation policies are multitudinous, fragmented, and overlapping, whereas Shenzhen's innovation policies are more targeted and more clearly differentiated, with a strong focus on strategic emerging industries. The two cities could strengthen their developing but weakly integrated CBRIS by collaborating in four areas of innovation policy: talent recruitment, joint R&D activities, enterprise competitiveness, and support for start-ups. The GBA initiative can succeed by driving innovation from a CBRIS perspective.